Comprehensive review on single-atom catalysts in electrochemical hydrogen-evolution reaction: computational modelling and experimental investigation - Fares Chabira; Sajjad Ali; Abbas Khan; Muhammad Humayun; Mohamed Bououdina (Philosophical Magazine Letters)
The growing demand for renewable energy sources has driven research efforts towards highly efficient electrochemical processes, especially the Hydrogen Evolution Reaction (HER) which is an essential component in renewable hydrogen production. Single Atom Catalysts (SACs) have been recognised as promising catalysts for exceptional HER activities owing to their unique electronic and geometrical features. This comprehensive review highlights the effective correlation between computational modelling and experimental research in fabricating new SACs and better understanding their catalytic mechanisms in the HER. Furthermore, the review briefly describes the choice of metals and tailoring the electronic structure, as well as exploring the influence of the reaction parameters on the catalytic activity of SACs for HER. Concluding remarks alongside future perspectives on the improvement of SACs for HER are emphasised. It is hoped that this review will pave the way for rational design of highly effective, low-cost and stable SACs for sustainable hydrogen production.